UNVEILING IMPLICIT MEANING: EXPLORING THE SUBTEXT OF EUPHEMISMS (Scientific journal of the Fergana State University, 2024)
Euphemisms, often employed to soften or conceal sensitive or taboo topics, carry not only their explicit meaning but also a rich tapestry of implicit meaning. This article delves into the intriguing realm of implicit meanings expressed in euphemisms. The Methods section of this exploration involves a comprehensive review of literature and linguistic analysis. The Results section presents an array of implicit meanings commonly associated with euphemisms. The Discussion section delves deeper into the implications of implicit meanings in euphemisms. Through an exploration of sub sections, we shed light on the complex subtext conveyed by euphemistic language.